Supernumerary Marker Chromosomes Derived From Chromosome 6: Cytogenetic, Molecular Cytogenetic and Array CGH Characterization - Huang, Bing (2012)
Supernumerary marker chromosomes (SMC) are relatively common in prenatal diagnosis. As the clinical outcomes vary greatly, a better understanding of the karyotype-phenotype correlation for different SMCs will be important for genetic counseling. We present two cases of prenatally detected de novo, small SMCs. The markers were present in 80% of amniocyte colonies in Case 1 and 38% of the colonies in Case 2. The SMCs were determined to be derived from chromosome 6 during postnatal confirmation studies. Although the sizes and the chromosomal origin of the SMCs in these two cases appeared to be similar, the clinical outcomes varied. The clinical manifestations observed in Case 1 included small for gestational age, feeding difficulty at birth, hydronephrosis, deviated septum and dysmorphic features, while the phenotype is apparently normal in Case 2. Array comparative genomic hybridization (CGH) was performed and showed increase in dosage for approximately 26 Mb of genetic material from the proximal short and long arms of chromosome 6 in Case 1. Results of array CGH were uninformative in Case 2, either due to mosaicism or lack of detectable euchromatin. The difference in the clinical presentation in these two patients may have resulted from the difference in the actual gene contents of the marker chromosomes and/or the differential distribution of the mosaicism.